2021
DOI: 10.1111/cpr.13134
|View full text |Cite
|
Sign up to set email alerts
|

D‐mannose alleviates osteoarthritis progression by inhibiting chondrocyte ferroptosis in a HIF‐2α‐dependent manner

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 57 publications
(99 reference statements)
0
57
0
Order By: Relevance
“…The role of ferroptosis in musculoskeletal diseases has been well documented [ 50 ]. Ferroptosis in chondrocytes leads to progression of osteoarthritis, which can be alleviated by inhibiting chondrocyte ferroptosis [ 51 , 52 ]. Studies using nucleus pulposus cells from both human and animal models have shown that ferroptosis is involved in intervertebral disc degeneration [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of ferroptosis in musculoskeletal diseases has been well documented [ 50 ]. Ferroptosis in chondrocytes leads to progression of osteoarthritis, which can be alleviated by inhibiting chondrocyte ferroptosis [ 51 , 52 ]. Studies using nucleus pulposus cells from both human and animal models have shown that ferroptosis is involved in intervertebral disc degeneration [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Nrf2 antioxidant system and ferroptosis regulate each other under inflammatory and iron overload conditions, although the detailed mechanism is still unclear [ 120 ]. A subsequent study also found that D-mannose, a compound involved in immune regulation, exerted a chondroprotective effect by attenuating the sensitivity of chondrocytes to ferroptosis and alleviating OA progression ( Figure 5(c) ) [ 121 ]. Through further research, GPx4 was shown to play an important role in the relationship between osteoarthritis and ferroptosis.…”
Section: Ferroptosis In Bone-related Diseasesmentioning
confidence: 99%
“…[ 119 ] with permission from 2020 Elsevier B.V.); (c) chondrocytes 24 h postindicated treatments by MitoTracker Red staining (reproduced from ref. [ 121 ] with permission from 2021 Ovid Technologies, Inc.); (d) mitochondrial membrane rupture in OA cartilage tissues by a transmission electron microscope (reproduced from ref. [ 122 ] with permission from 2022 Elsevier B.V.); (e) three-dimensional models of mouse knee joints.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of injection of DFO in OA mice was also demonstrated in vivo [ 73 ]. Similarly, Zhou et al [ 74 ] investigated whether D-mannose mediates chondrocyte ferroptosis during OA cartilage degeneration in vitro and in vivo . They found that D-mannose could exert a chondroprotective effect by attenuating the sensitivity of chondrocytes to ferroptosis and could alleviate OA progression.…”
Section: Ferroptosis and Bone Degenerative Disordersmentioning
confidence: 99%